Архітектурно-планувальна організація комунікативного простору у структурі торгово-розважальних центрів - Березко, Олена Володимирівна (Національний університет "Львівська політехніка", 2017)
У дисертаційній роботі уточнено дефініцію поняття «комунікативний простір ТРЦ». На основі аналізу вітчизняного та закордонного досвіду будівництва та експлуатації комунікативних просторів ТРЦ за критеріями функціонального наповнення, метричних характеристик, композиційного вирішення розроблена типологія комунікативних просторів відповідно до розмірів, типу планувальної організації, набору функціональних зон, типу планувальної організації функціональних зон. Запропоновано розглядати комунікативний простір як редукований регульований міський центр. Запропоновані принципи архітектурно розпланувальної організації комунікативних просторів (ергономічний, органічний, принцип соціальної відкритості, принцип гармонійності, принцип гнучкості та поліфункціональності). До кожного із принципів розроблено типологічні, метричні та естетичні рекомендації. В диссертационной работе уточнено дефиницию понятия «коммуникативное пространство ТРЦ». Проведен анализ отечественного и зарубежного опыта строительства и эксплуатации коммуникативных пространств ТРЦ по критериям функционального наполнения, метрических характеристик и композиционного решения. Основываясь на результатах анализа, в работе разработана типология коммуникативных пространств в соответствии с размерами, типом архитектурно-планировочной схемы, набором функциональных зон и в соответствии с превосходящим по размеру элементом. Предложено рассматривать коммуникативное пространство как регулируемый аналог центра города. Предложены принципы архитектурно-планировочной организации коммуникативных пространств ТРЦ (эргономичный, органический, принцип социальной открытости, принцип гармоничности, принцип гибкости и полифункциональности). К каждому из принципов разработаны типологические, метрические и эстетические рекомендации. This thesis clarifies the definition of “shopping mall’s social space” concept. In the work author analyzed domestic and international experience of shopping malls’ social spaces development and operation by the criteria of functional content, metric characteristics and compositional solution. In the first chapter the literature review on the research topic was conducted. Based on the review, the term “shopping mall’s social space” was formulated. Author determined that department stores as well as shopping arcades and galleries were the prototypes of modern malls, and the mall itself is a combination of architectural and planning approaches used in the abovementioned building types design. In the second chapter author analyzed already-established research methods of socio-cultural objects and public complexes, particularly shopping malls. Based on this analysis, systematic approach was identified as the main one for this study. In this chapter structural analysis of shopping mall using the general concepts of system analysis was conducted as well as the analysis of social space functioning as mall’s subsystem using the method of the “black box”. Based on this model the general structure of further research was formed. Also the empirical research base was formed which consists of the analysis of shopping malls located in Western Europe and Ukraine. The methodological sequence was developed for more detailed study of the 30 selected malls. In the third chapter the architectural factors of influence were defined: urban location, construction site profile, size of shopping mall, conditions of construction, aesthetics and design features; as well as economic, marketing, climatic, ecological, social and psychological ones. Author conducted the analysis of these factors’ impact on the formation of architectural and planning design of social space. Also in this chapter the following architectural means of space design were analysed: three-dimensional organization, architectural-planning layout, tectonic expression, rhythmic organization, scale, means of navigation, color and lighting solutions, interior objects. In the fourth chapter author developed a social spaces typology according to size, planning layout type, set of functional areas and their planning layout type. Author proposed to consider a social space as a reduced and controlled city center as well as principles of architectural design and planning layout of social spaces (ergonomic, organic, principle of social openness, principle of harmony, flexibility and multifunctionality). Each of the principles is supported by developed typological, metric and aesthetic guidelines.
Архитектурно-планировочная организация коммуникативного пространства в структуре торгово-развлекательных центров
Architectural design and planning layout of a social space within a shopping mall structure
Keywords: комунікативний простір; торгово-розважальний центр; архітектурно-планувальна організація; типологія; коммуникативное пространство; торгово-развлекательный центр; архитектурно-планировочная организация; типология; social space; shopping mall; architectural design; planning layout; typology